THE EFFECT OF E-SAMSAT IMPLEMENTATION, TAX KNOWLEDGE, SERVICE QUALITY, AND TAX SANCTIONS ON MOTOR VEHICLE TAXPAYER COMPLIANCE IN EAST SURABAYA - Congda, Lysia (Krisnadwipayana International Journal of Management Studies, 2022)
One of the things that affects the taxpayer in carrying out his obligations as a good citizen is compliance in paying taxes. Taxpayer compliance is an important factor in realizing tax revenue targets. The higher the compliance of the taxpayer, the higher the tax revenue will increase, and vice versa. The questionnaire used in this study were 100 questionnaire with the determination of samples is using the method of accidental sampling. Data collection is done by questionnaire method. There are several research methods used to achieve this research objective including descriptive statistical analysis, validity test, rehabilitation test, classical assumption test (normality test, multicollinearity test, heteroskedasticity test), multiple linear regression analysis, and t test.The results of this study show that the application of E -Samsat and tax sanctions has a positive effect on the compliance of motor vehicle taxpayers in East Surabaya. While The Knowledge of Taxation, and Quality of Service has no effect on the compliance of east Surabaya motor vehicle taxpayers.